ISLAMIC ECONOMIC INTEGRATION : OPPORTUNITIES AND CHALLENGES IN ESTABLISHING A UNIFIED ISLAMIC ECONOMIC BLOC - Hana Mabrukah (JURNAL PROFIT, 2025)
Islamic economic integration as an effort to build a coordinated and stable Islamic economic bloc. In the context of increasingly complex globalization, member countries have various opportunities to enhance cooperation in trade, investment, and human resource development. However, major challenges are also faced, including regulatory differences, political instability, and inadequate infrastructure. This study analyzes the possible benefits of Islamic economic integration, as well as increased competition and social justice, and identifies the strategic measures needed to overcome the obstacles. Through open dialog and cross-sectoral cooperation, countries in the Islamic economic bloc can create a solid foundation for inclusive and sustainable economic growth and contribute significantly to the global economy. This article also discusses the importance of education and training to increase the capacity of human resources in the field of Islamic economics. A focus on understanding Shariah principles and ethical business practices is key to encouraging the active participation of economic actors. In addition, this study highlights the need for harmonization of regulations and policies among member countries to create a more favorable business environment. Through close cooperation between Islamic financial institutions and government agencies. The government should optimize resource allocation and expand access to funding. The importance of building an international cooperation network to enhance the competitiveness of Islamic economic blocs in the global market. By combining strengths and resources, member countries can overcome challenges and take advantage of opportunities, so that the Islamic economic bloc can develop sustainably and provide more benefits to society.